Examining the relationship between meeting 24-hour movement behaviour guidelines and mental health in Chinese preschool children - Yin, Long; Li, Fang; Liu, Pan; Yin, Zhiqiang; Yang, Zongyu; Pi, Linchun; Gao, Zan (Frontiers in Pediatrics, 2024)
Background: Limited research has explored the relationship between adhering to 24-hour Movement Behaviour guidelines and mental health in Chinese preschool children. The objectives of this study encompassed two primary goals: (1) to investigate the adherence of preschool children in China to the 24-hour Movement Behaviour guidelines; and (2) to analyze the relationship between fulfilling various combinations of these guidelines and mental health, identifying the most advantageous combination. Methods: Utilizing a convenience sampling approach, this study included 205 preschool children (117 boys and 88 girls, average age 4.8 ± 0.51 years) from five kindergartens in Hengyang, Hunan Province.The physical activity (PA) and sedentary behaviour of preschool children were objectively assessed using waist-worn accelerometers, while sleep duration and screen time were reported by the children's parents. To evaluate mental health, the parent version of the internationally validated Strength and Difficulties Questionnaire (SDQ) was employed, which measures externalizing problems, internalizing problems, and prosocial behaviour. Employing Mplus 8.0 for Structural Equation Modeling analysis, while controlling for demographic variables, the study explored the connection between preschool children's mental health and their adherence to the 24-hour Movement Behaviour guidelines.Results: Worryingly, merely 14.6% of preschoolers met the recommended guidelines for all three aspects. Positive correlations were identified between meeting PA guidelines and displaying prosocial behaviour (β = 0.184; p < 0.05), while screen time adherence exhibited a negative correlation with externalizing problems (β=-0.207; p < 0.05). Similarly, there was a negative association between sleep duration adherence and externalizing problems (β = -0.191; p < 0.05).Meeting all three recommended guidelines was notably linked to enhanced prosocial behaviour (β = 0.464; p < 0.05), while following the screen time and sleep duration guidelines was negatively associated with externalizing problems (β = -0.246; p < 0.05).: This study underscores the limited adherence of Chinese preschoolers to the comprehensive 24-hour Movement Behaviour guidelines. Noteworthy findings include the positive influence of PA on prosocial behaviour, alongside the significant roles that sleep duration and screen time play in mitigating externalizing problems within this age group. Alignment with the 24-hour Movement Behaviour guidelines is associated with more favorable mental health indicators in preschoolers.